Nepenthes Ampullaria (Nepenthaceae) pitchers are unattractive to Gravid Aedes Aegypti and Aedes Albopictus (Diptera: Culicidae) - Chou, L.; Dykes, Gary; Wilson, R.; Clarke, C. (Entomological Society of America, 2016)
Nepenthes pitcher plants are colonized by a variety of specialized arthropods. As Aedes mosquitoes are container breeders, Nepenthes pitchers are a potential candidate oviposition site for vector species, such as Aedes aegypti (L.) and Aedes albopictus (Skuse). However, Aedes spp. are not commonly encountered in Nepenthes pitchers, and the environment inside the pitchers of some species is lethal to them. One exception is Nepenthes ampullaria Jack, whose pitchers are known to be colonized by Ae. albopictus on very rare occasions. Given that Ae. albopictus larvae can survive in N. ampullaria pitcher fluids, we sought to determine why pitcher colonization is rare, testing the hypothesis that gravid Aedes mosquitoes are deterred from ovipositing into container habitats that have similar characteristics to N. ampullaria pitchers. Using plastic ovitraps of different sizes, colors, and with different types of fluids (based on the characteristics of N. ampullaria pitchers), we compared oviposition rates by Aedes mosquitoes in urban and rural areas within the geographical range of N. ampullaria near Kuala Lumpur, Malaysia. Ovitraps that were black and large (>250-ml capacity) accumulated significantly more eggs than ovitraps that were smaller, or green in color. In terms of size and color, small, green ovitraps are analogous to N. ampullaria pitchers, indicating that these pitchers are not particularly attractive to gravid Ae. albopictus. Although Aedes spp. are capable of colonizing N. ampullaria pitchers, the pitchers are relatively unattractive to gravid females and do not represent a significant habitat for larvae of dengue vectors at present.